2023
DOI: 10.3389/fendo.2023.1142276
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy by natural polyphenols in the treatment of diabetic kidney disease: therapeutic potential and mechanism

Tongtong Liu,
Qi Jin,
Liping Yang
et al.

Abstract: Diabetic kidney disease (DKD) is a major microvascular complication of diabetes and a leading cause of end-stage renal disease worldwide. Autophagy plays an important role in maintaining cellular homeostasis in renal physiology. In DKD, the accumulation of advanced glycation end products induces decreased renal autophagy-related protein expression and transcription factor EB (TFEB) nuclear transfer, leading to impaired autophagy and lysosomal function and blockage of autophagic flux. This accelerates renal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 175 publications
0
1
0
Order By: Relevance
“…In recent decades, natural products (NPs) sourced from plants, animals, and microorganisms have attracted increased attention given their multifaceted components, ability to target multiple pathways, accessibility, and low toxicity levels ( Newman and Cragg, 2016 ; Newman and Cragg, 2020 ). Recent studies have increasingly demonstrated the therapeutic potential of NPs in DR, DKD, DC, and DPN by modulating autophagy ( Yao et al, 2018 ; Zhou P. et al, 2019 ; Yin et al, 2021 ; Liu P. et al, 2023 ; Liu T. et al, 2023 ). This article reviews recent research on autophagy and DMC, exploring the role and mechanism of NPs in enhancing DMC efficacy by regulating autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, natural products (NPs) sourced from plants, animals, and microorganisms have attracted increased attention given their multifaceted components, ability to target multiple pathways, accessibility, and low toxicity levels ( Newman and Cragg, 2016 ; Newman and Cragg, 2020 ). Recent studies have increasingly demonstrated the therapeutic potential of NPs in DR, DKD, DC, and DPN by modulating autophagy ( Yao et al, 2018 ; Zhou P. et al, 2019 ; Yin et al, 2021 ; Liu P. et al, 2023 ; Liu T. et al, 2023 ). This article reviews recent research on autophagy and DMC, exploring the role and mechanism of NPs in enhancing DMC efficacy by regulating autophagy.…”
Section: Introductionmentioning
confidence: 99%